إعداد دليل منهجي للتشخيص والتقويم في العملية الإرشادية موجه للمرشد المبتدئ - بوعافية بلقيس; اكرام علال (جامعة الوادي - University of Eloued, 2025)
"تهدف هذه الدراسة المعنونة بإعداد دليل منهجي لتشخيص والتقويم في العملية الإرشادية إلى تسهيل وتوضيح للمرشد المبتدئ كيفية تطبيق خطوات التشخيص والتقويم في العملية الإرشادية. حيث تم الإعتماد على المنهج الوصفي التحليلي لتوصل إلى أهداف الدراسة وفهم محتواها، لأجل تحديد المفاهيم المرتبطة بالتشخيص والتقويم، والتعرف على الخطوات والمراحل. الأساسية في العملية الإرشادية والذي يركز على، تشجيع المسترشد لإكتساب الخصائص التي تؤدي إلى تحقيق الذات، مثل الإنفتاح على الخيرات، والثقة بالنفس وتطوير مركزاً داخلياً لضبط والتقييم الذاتي، وبالتالي زيادة قدرة الفرد على التخلي والتأثير في ضبط تصرفاته. و طرحت لهذه الدراسة الفرضية التالية: ما لغاية المرجوة من إعداد دليل منهجي للمرشد المبتدئ، في شكل تساؤول رئيسي وتحليلي وبالتالي تم الإعتماد على المنهج الوصفي التحليلي. ولتحقيق كيفية سيرورة العملية الإرشادية تم إجراء مقابلة كنموذج إرشادي للمرشد المبتدئ على عينة تتكون من أربعة (4) تلاميذ (مسترشدين) بالمؤسسة التربوية مستوى ثالثة ثانوية (البكالوريا) المساعدة المرشد للتعرف على مشكلاتهم أثناء العملية الإرشادية عن طريق التشخيص والتقويم. أما بالنسبية لتحقيق هذا العمل، فقد تم من خلال الخطوات التالية: • إعداد بروتوكول المقابلة الإرشادية. • الاعتماد على المقابلة الإرشادية في جمع المعلومات. • إجراء المقابلات مع المسترشدين بعد إعداد بروتوكول المقابلة الإرشادية. • إعداد دليل منهجي التشخيص والتقويم في العملية الإرشادية موجه للمرشد المبتدئ. ""This study, entitled ""Preparing a Methodological Guide for Diagnosis and Evaluation in the Counseling Process,"" aims to facilitate and clarify for novice counselors how to apply the steps of diagnosis and evaluation in the counseling process. The descriptive analytical approach was used to achieve the study's objectives and understand its content. It also aimed to define the concepts associated with diagnosis and evaluation, and to identify the basic steps and stages of the counseling process. This approach focuses on encouraging clients to acquire the characteristics that lead to self-realization, such as openness to good things, self-confidence, and the development of an internal center for self-control and self-evaluation. This, in turn, increases the individual's ability to let go and influence their behavior. This study proposed the following hypothesis: What is the desired goal of preparing a methodological guide for novice counselors? This hypothesis was presented in the form of a main and analytical question. Therefore, the descriptive analytical approach was adopted. To determine how the counseling process operates, an interview was conducted as a model for the novice counselor. A sample of four (4) students (counselored) at the educational institution, at the third secondary level (Baccalaureate), was used to assist the counselor in identifying their problems during the counseling process through diagnosis and evaluation. To achieve this goal, the following steps were taken: • Preparing the counseling interview protocol. • Relying on the counseling interview to gather information. • Conducting interviews with counselors after preparing the counseling interview protocol. • Preparing a methodological guide for diagnosis and evaluation in the counseling process, directed at novice counselors. "
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص إرشاد وتوجيه
Keywords: المرشد المبتدئ; العملية الإرشادية; التشخيص والتقويم; إعداد دليل منهجي; Preparing a methodological guide; Diagnosis and evaluation; Counseling process; Novice counselor